2010
DOI: 10.1111/j.1467-8683.2009.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Board Monitoring in Family‐owned Companies: Evidence from Asia

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: We propose that high levels of monitoring are not always in the best interests of minority shareholders. In family-owned companies the optimal level of board monitoring required by minority shareholders is expected to be lower than that of other companies. This is because the relative benefits and costs of monitoring are different in family-owned companies. Research Findings/Insights: At moderate levels of board monitoring, we find concave relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 67 publications
6
47
0
Order By: Relevance
“…Furthermore, we find that the voting rights of the second-largest shareholder, the presence of several large shareholders beyond the largest shareholder and their aggregate and relative (to the dominant shareholder) voting rights are strongly and positively associated with CRT. In additional tests, we find that the effect of MLS on CRT is more pronounced in the firms in which the dominant shareholder is a Family, supporting the findings in prior literature that Family-dominated firms have severe agency problems (e.g., Bae et al, 2002;Boubakri et al, 2010;Chen & Nowland, 2010;Shyu & Lee, 2009).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, we find that the voting rights of the second-largest shareholder, the presence of several large shareholders beyond the largest shareholder and their aggregate and relative (to the dominant shareholder) voting rights are strongly and positively associated with CRT. In additional tests, we find that the effect of MLS on CRT is more pronounced in the firms in which the dominant shareholder is a Family, supporting the findings in prior literature that Family-dominated firms have severe agency problems (e.g., Bae et al, 2002;Boubakri et al, 2010;Chen & Nowland, 2010;Shyu & Lee, 2009).…”
Section: Resultssupporting
confidence: 85%
“…Finally, we find that the strong positive association between CRT and MLS holds in family-controlled firms, but this association disappears in non-family firms. This finding supports the prior literature that demonstrates a widespread expropriation of minority shareholders (e.g., Bae, Kang, & Kim, 2002;Bertrand, Mehta, & Mullainathan, 2002;Boubakri, Guedhmai, & Mishra, 2010;Shyu & Lee, 2009), a lack of board independence including sub-optimal monitoring (Chen & Nowland, 2010) and incentives to expropriate due to control rights in excess of cash flow rights (Chen & Nowland, 2010;Shyu & Lee, 2009) in family-controlled firms in this region. For example, both Bae et al (2002) and Bertrand et al (2002) uncovered extensive expropriation and tunneling in Korean Chaebols.…”
Section: Introductionsupporting
confidence: 90%
“…We also test the effectiveness of an independent director on mitigating Type II agency problems in family firms. Prior studies investigating the role of independent directors on management oversight have found that less severe Type II agency problems occur in the presence of strong monitoring and protection of minority shareholders' interests, thus helping to mitigate Type II agency problems (Chen & Nowland, 2010). We thus propose that board independence moderates the relationship between family control and investment-cash flow sensitivity.…”
Section: Introductionmentioning
confidence: 80%
“…As families learn about the 'familiness' of their resources and are able to imprint this learning onto following generations, they willover time -become better qualified to fulfil the value protection role through family representatives on the board rather than outsiders (Chrisman et al, 2013;Sirmon and Hitt, 2003). In contrast, in young family-owned companies, the optimal level of board monitoring required by minority shareholders is found to be lower than that of other companies (Chen and Nowland, 2010). The high information asymmetry between the young family firm and outsiders means that monitoring by independent directors is less effective in young familyowned companies than in other companies.…”
Section: Family Firmsmentioning
confidence: 97%